The Impact of Quantum Teaching Strategy on Student Academic Achievement and Self-Esteem in Inclusive Schools (Malaysian Journal of Learning and Instruction, 2014)
Purpose â€“ This research was aimed at showing the impact of a teaching strategy called the Quantum Teaching Strategy on studentsâ€™ academic achievements in two school subjects, namely in Bahasa Indonesia and Science, in comparison to that experienced through classes using a conventional teaching strategy. This research also examined the role of self-esteem on the studentsâ€™ academic achievements in both the subjects in inclusive schools in Indonesia. Methodology â€“ This research was a quasi-experimental study on two intact groups of sixth graders of two different inclusive schools. The sample was assigned through multi-staged cluster sampling from 78 elementary schools in 15 sub-district areas. The data on student academic achievements was collected by means of tests, while the data on self-esteem were obtained through a questionnaire. T-test was used to analyze the different impacts of the Quantum Teaching Strategy and conventional teaching strategy on the academic achievements of students, while ANCOVA was applied to determine whether the studentsâ€™ self-esteem infl uenced their academic achievements in Bahasa Indonesia and Science. Findings â€“ The t-test showed that the Quantum Teaching Strategy had a better impact on both Bahasa Indonesia and Science achievements as compared to the conventional teaching strategy. Significance â€“ Findings of this study can be used as a guide for planning and using Quantum Teaching Strategy in teaching and learning Bahasa Indonesia and Science in inclusive schools.